Effect on insulin, glucose and lipids in overweight/obese australian adults of 12 months consumption of two different fibre supplements in a randomised trial - Pal, Sebely; Ho, Suleen; Gahler, R.; Wood, S. (MDPI Publishing, 2017)
Higher fibre intakes are associated with risk reduction for chronic diseases. This study investigated the effects of supplementation with PolyGlycopleX® (PGX), a complexed polysaccharide, on insulin, glucose and lipids in overweight and obese individuals. In this double-blind 12 months study, participants were randomised into three groups: control (rice flour), PGX or psyllium (PSY). Participants followed their usual lifestyle and diet but consumed 5 g of their supplement before meals. Insulin was significantly lower in the PGX and PSY groups compared to control at 3 and 6 months and in the PSY group compared to control at 12 months. Serum glucose was significantly lower in the PGX group at 3 months compared to control. Total cholesterol was significantly lower in the PGX and PSY groups compared to control at 3 and 6 months. High density lipoprotein (HDL) cholesterol was significantly increased in the PGX group compared to control at 12 months. low density lipoprotein (LDL) cholesterol was significantly lower in the PGX group at 3 and 6 months compared to control and in the PSY group at 3 months compared to control. A simple strategy of fibre supplementation may offer an effective solution to glucose, insulin and lipid management without the need for other nutrient modification. © 2017 by the authors; licensee MDPI, Basel, Switzerland.